The Effect of Internship Programs on Subsequent College Performance. - Koehler, Robert W. (The Accounting Review, 1974)
Abstract The article focuses on the hypotheses that there is a tendency for students to improve academically and to realize more fully the value of communication skills following their participation in an internship program. Participants in The Pennsylvania State University's 23-year-old program were used to test these hypotheses. Penn State has a large program with a wide geographical representation. Last winter 78 interns were placed among 16 firms in 19 locations. Altogether 45 offices were represented. Internship programs are part of the academic curriculum at an increasing number of schools. They provide an efficient way to involve students in real live situations. Students can apply and reinforce their classroom knowledge. Their periodic reviews help them to better understand their strengths and weaknesses. They can evaluate competing employment opportunities before making a permanent commitment. They show that there is a tendency for both accounting and general grades to improve following an internship.